(untitled) (Comprehensive Journal of Science, 2025)
The mechanical properties of reinforcing steel bars are critical to the longevity and performance of architectural structures, including buildings, skyscrapers, and bridges. The integrity and endurance of reinforced concrete constructions heavily rely on specific properties of the reinforcing bars, such as tensile strength, bendability, fatigue resistance, weldability, and ductility. Steel exhibits a wide range of mechanical characteristics of which the strength factor is the dominant property. Engineering strength is evaluated in terms of yield strength YS, ultimate tensile strength UTS, modulus of elasticity, percentage elongation and impact strength. Thus, any increase in strength characteristics of steel will enhance the reliability and durability of the structure in which it is used. Low strength characteristics often result in short life span of the structure, undesirable deflection and even collapse. The methodology for this study involved research is to perform a comparative analysis of the mechanical properties of steel bars diameter 14mm for produced by Seedy Al-Saih Steel Factory (SASF) and Zliten Steel Factory (ZSF), focusing on adherence to international standards. And local standards (SASF) steel bars manufactured locally in Libya from recycled scrap showed that the mechanical properties (yield strength, ultimate tensile strength, elongation, hardness, , chemical composition) were consistent with Libyan and international standards (ASTM). In contrast, for the Zliten Iron and Steel Factory, which also uses scrap in the production of steel bars, the value average mechanical properties (yield strength, tensile strength, elongation, hardness, and chemical composition) were slightly higher than the Libyan standard LY and the international standard ASTM. And It is strongly advised that additional advancements be made in the chemical composition, which primarily influences the mechanical characteristics of steel bars, in order to grow the Libyan steel industry and keep the quality of lightweight goods within regional and global standards